Municipal Solid Waste Management in Perlis: status, Problem and Challenge - Boonsie, Cassryreenne Bun Chu (Penerbit Universiti Malaysia Perlis, 2011)
Current solid waste management was a major problem in most developing countries. Interview and questionnaires survey on SWM has been done to identify the current status, problems and challenges in Perlis. From the research survey done, there were lot of problems occur in this state. Among them are unproper solid wastes disposal, rubbish are not regular arranged, lack of waste container, along with inefficient waste collection and transportation processes. Other problems are lack of management and maintenance of compactor lorry and poor public awareness on SWM problem. Besides, there is no recycle method been done for now such as low implementation in 3R programmed. Disposal site around Perlis never been provided with a proper treatment and the method of dispose also uncontrollable. Among them are open burning and illegal dumping which is increased the environmental pollution. Therefore, study on leachate characteristics at Padang Siding open dumping has been done. pH data acquired for three different sampling locations is in the range of 6.5 to 7.22, which is acidic. BOD is between 14.98 mg/L to 18.53 mg/L while COD shows the range between 3023.35 mg/L to 3870 mg/L. Ammoniacal Nitrogen is higher that is around 11.29 mg/L to 151.4mg/L. Data for ion Chromium Hexavalent is in the range of 0.185 mg/L to 0.555 mg/L, while Zinc is around 2.68mg/L to 2.87 mg/L. The value of pH and BOD however are lower than the limit set in Environmental Quality (Sewage and Industrial Effluent), 1979 while other parameter are over Standard A limit.